Three-bond sugar-base couplings in purine versus pyrimidine nucleosides: a DFT study of Karplus relationships for (3)J(C2/4-H1') and (3)J(C6/8-H1') in DNA - Munzarová, Markéta L; Sklenár, Vladimír (Journal of the American Chemical Society, 2002)
(3)J(C2/4-H1') and (3)J(C6/8-H1') scalar spin-spin coupling constants have been calculated for deoxyadenosine, deoxyguanosine, deoxycytidine, and deoxythymidine as functions of the glycosidic torsion angle chi by means of density functional theory. Except for deoxythymidine, (3)J(C2/4-H1') depends little on the base type. On the contrary, (3)J(C6/8-H1') follows the usual trans to cis ratio ((3)J(C-H(cis)) < (3)J(C-H(trans))) for purine nucleosides, but reveals the opposite relation ((3)J(C-H(cis)) > (3)J(C-H(trans))) for pyrimidine nucleosides. Our results compare well with the experiment for deoxyguanosine and predict a novel trend in the case of pyrimidine bases for which no NMR results are available in the syn region. A breakdown of the key Fermi contact part of (3)J(C6/8-H1') into MO contributions rationalizes this trend in terms of an unusual coupling mechanism in the syn orientation that is very effective for pyrimidine nucleosides and considerably weaker for purine nucleosides.
Keywords: purinové nukleosidy; Purine Nucleosides; Models, Molecular; molekulární modely; nukleární magnetická rezonance biomolekulární; DNA; Pyrimidine Nucleosides; Nuclear Magnetic Resonance, Biomolecular; pyrimidinové nukleosidy